2016
DOI: 10.1007/s10461-016-1385-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Power and Sexual Violence Among HIV-Positive Women in Rural Uganda

Abstract: Gender-based power imbalances place women at significant risk for sexual violence, however, little research has examined this association among women living with HIV/AIDS. We performed a cross-sectional analysis of relationship power and sexual violence among HIV-positive women on anti-retroviral therapy in rural Uganda. Relationship power was measured using the Sexual Relationship Power Scale (SRPS), a validated measure consisting of two subscales: relationship control (RC) and decision-making dominance. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 73 publications
3
18
1
Order By: Relevance
“…On average SRPS values for women in this study were consistent with studies of nondrug using women (Conroy et al, 2016; Muldoon et al, 2015), but lower than RC and DMD values reported in a study of drug-involved women (Campbell et al, 2012). Significant findings emerge that provide support for the importance of sexual relationship power dynamics in the context of sexual behaviors for WWID.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On average SRPS values for women in this study were consistent with studies of nondrug using women (Conroy et al, 2016; Muldoon et al, 2015), but lower than RC and DMD values reported in a study of drug-involved women (Campbell et al, 2012). Significant findings emerge that provide support for the importance of sexual relationship power dynamics in the context of sexual behaviors for WWID.…”
Section: Discussionsupporting
confidence: 88%
“…The SRPS has primarily been applied to nonsubstance using heterosexual partnerships in the field of HIV prevention research (Campbell et al, 2009; Conroy et al, 2016; Muldoon, Deering, Feng, Shoveller, & Shannon, 2015), in which lower SRPS scores have been associated with higher risk and inconsistent condom use and for HIV infection (Bonacquisti & Geller, 2013; Dunkle et al, 2004; Jewkes, Dunkle, Nduna, & Shai, 2010). However, we are unaware of any investigation of relationship dynamics in the intersecting injecting and sexual relationships of young WWID, or one that quantifies the impact of sexual relationship power on injecting or sexual risk behaviors in the context of WWID’s sexual relationships.…”
Section: Introductionmentioning
confidence: 99%
“…41 Other studies have, in turn, found that relationship power inequities are determinants of HIV transmission risk. 42,43 In order to comprehensively address HIV disclosure concerns among women, future research is needed to understand the role of community norms in influencing relationship power inequities and risky sex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely shown that alcohol is a risk factor for sexual violence and viceversa [10,11,37,38,67]. Alcohol may cause aggressive behaviors as a result of a distortion in the perceptions or of a disinhibition [6], it can also make it more difficult for the victims to protect themselves or it can even bring the victims to places where they have a greater risk of meeting a potential offender [3,9,6870]. It is a relevant aspect to be considered in sexual violence prevention and in HIV VCT for adults and young people in the DRC, where a high percentage of adolescents both use alcohol and are sexually active [9].…”
Section: Discussionmentioning
confidence: 99%